1996
DOI: 10.1097/00003072-199605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Gastric Emptying in Patients With Systemic Sclerosis

Abstract: Gastric emptying studies, using an indigenously prepared radiolabeled solid food marker in the form of Indian bread called Chapati, were performed on 13 patients with systemic sclerosis. Six patients had limited cutaneous disease and seven had diffuse cutaneous disease. Earlier, the procedure was standardized in 30 healthy volunteers. Seven of the 13 (54%) patients (five with diffuse and two with limited cutaneous disease) had delayed gastric emptying. Most of these patients had gastric symptoms. This pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Among 12 symptomatic patients with advanced SSc who underwent radioscintigraphy, 75% were found to have delayed gastric emptying (18). In other small series of SSc patients evaluated by scintigraphy, 50–67% of the patients showed delayed gastric emptying (16, 19–23).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Among 12 symptomatic patients with advanced SSc who underwent radioscintigraphy, 75% were found to have delayed gastric emptying (18). In other small series of SSc patients evaluated by scintigraphy, 50–67% of the patients showed delayed gastric emptying (16, 19–23).…”
Section: Discussionmentioning
confidence: 86%
“…Delayed gastric emptying is a severe condition in SSc patients. Nevertheless, previous studies of delayed gastric emptying are rare and have included only a small number of patients with symptomatic SSc, who were evaluated using either radioscintigraphy or ultrasonography (15–23). Among 12 symptomatic patients with advanced SSc who underwent radioscintigraphy, 75% were found to have delayed gastric emptying (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic transit time using a previously validated protocol (20 markers each at 0, 12 and 24 hour; abdominal radiographs at 36 and 60 hour) showed 54 of 60 markers retained at 60 hour (abnormal > 14 markers) suggestive of slow colonic transit (Figure). 6 Radionuclide gastric emptying study using technetium 99-m sulfur colloid labeled standard solid meal showed clearance half time of 61 minutes (normal 83 ± 13 minutes) 7. Glucose hydrogen breath test using a standard protocol (Quin Tron Breathtracker™ Digital Microlyzer, QuinTron Inc, Milwaukee, WI, USA) revealed rise in breath hydrogen from 13 parts per million (ppm) in fasting state to 36 ppm after ingestion of 100 g glucose (abnormal > 12 ppm than basal) suggesting small intestinal bacterial overgrowth (Figure; sensitivity 44% and specificity 80%) 8.…”
Section: Case Reportmentioning
confidence: 99%
“…In an autopsy study, GI muscle atrophy and fibrosis (both of which lead to decreased GI motility) were detected in the esophagus, small intestine, and colon in 74%, 48%, and 39% of patients, respectively [3]. In previous studies, 50-67% of patients with SSc report delayed gastric emptying, which correlates with symptoms of early satiety, bloating, and emesis [4][5][6][7][8][9][10][11][12]. At present, the cause of scleroderma is still unknown, and there are no effective treatments for SSc.…”
mentioning
confidence: 99%